Plan de continuidad de negocios del área de ventas de una empresa dedicada a la comercialización de tableros aglomerados por el período terminado el 31-12-2008 en la ciudad de Guayaquil - Aldaz, K. (2009)
The work that is presented subsequently consisted in the execution of an Accounts receivable- Incomes Audit of a business area dedicated to the commercialization of piled up panels in the city of Guayaquil during the year 2007. The development of this work had as purpose to perform the analysis of the areas that have significant risk and the reasonableness of these, for which the evaluation of fraud was done taking like fundamental reference the evidence of fraud obtained and the answer of the Management before uncertain fraudulent facts. The calculation of the outward appearance was carried out taking as base the utility before taxes, our professional judgment and certain factors that influenced for its calculation; analytic procedures were executed to obtain evidence through the comparisons of financial states, besides the analysis of each one of the components of the business internal control that was carried out. Then we design the risk matrix where the areas with significant risk were identified and with this the development of the substantive tests designs. Finally, they bring the conclusions and recommendations to the ones that we could reach after culminating the execution of this work.